Astrologia Talesa - Przybysławski, Artur (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2004)
The aim of the text is to show Thales not as an early primitive thinker but as an inventor of the new discourse that later will be called philosophical. Nevertheless Thales remained at the same time mythological sage faithful to Greek religion. The subtle and complicated relation between logos and mythos is showed as a background of the one-many problem so crucial for the European thought.